Evaluation of the risk for pressure ulcers in bedridden elderly at home - Moraes,Geridice Lorna de Andrade (2012)
OBJECTIVE: To evaluate the risk for pressure ulcers in elderly in their homes, after a period of hospitalization. METHODS: A longitudinal prospective study conducted in the homes of 40 elderly identified with risk for pressure ulcer (PU) at hospital discharge, using the Braden Scale. The monitoring was conducted over four home visits, in the period between June and August of 2010, in Fortaleza (CE) and its metropolitan region. RESULTS: The majority of the elderly were female (65%) with a medical diagnosis of cerebral vascular accident (55%). In the first and second visits, 55% and 40% of the elderly, respectively, presented high risk for PU, and the incidence of PU was 22.5%. The association of the risk scores presented significant association in the first three visits. CONCLUSION: The risk for PU development was higher in the first two weeks, after hospital discharge, but diminished for the remainder of the visits.